Dynamic analysis of long-span bridge subjected to traffic loading - Gong, Lei (University of Ottawa (Canada), 2008)
Moving vehicle loads, associated with roadway traffic can induce significant dynamic effects in the structural behavior of bridges, especially for long-span bridges. The main objective of this research is to study traffic induced dynamic responses of long-span bridges, particular for box-girder bridges and cable-stayed bridges. The finite element method has been employed in this study to obtain a three-dimensional mathematical model for the bridge system. For box-girder bridges, the deck, the box girders and the diaphragms are modeled as 8-node shell element. Linear elastic structural responses are considered. For cable-stayed bridges, the box-girder bridge deck and diaphragms are modeled as 8-node shell element, while the pylons are modeled as beam element. Stability functions are applied to both shell element and beam element to account for geometric nonlinearity. A two-node catenary cable element is adopted using exact analytical expressions for modeling stayed cables. Non-linear structural responses are considered. For the present analytical study of the bridge-vehicle system, the vehicle is modeled as a three-axle six-wheel system. The equation derivations are described in details. The dynamic response is evaluated using the modal method and the step-by-step integration method. The natural frequencies and mode shapes of the bridge are obtained based on the deformed dead load tangent stiffness matrix. For cable-stayed bridge, an iterative scheme is utilized to obtain the deformed dead load tangent stiffness matrix due to its nonlinear characteristics. The dynamic responses of bridges subjected to traffic loads are complicated because the dynamic effect induced by moving vehicles is basically influenced by the interaction between the bridge and the moving vehicle. The bridge-vehicle interaction is affected by many factors, such as vehicle speed, road roughness, damping of bridge and vehicle, dynamic characteristics of bridge, and etc. Parametric study has been carried out to investigate those factors that influence the bridge-vehicle interaction. The finite element computer program GLBA in FORTRAN 90 and MATLAB is developed to carry out the proposed research. GLBA includes four main modules: static linear analysis, static non-linear analysis, free vibration analysis and dynamic analysis due to traffic load.
Keywords: Engineering, Civil.